2022
DOI: 10.1128/mbio.01891-22
|View full text |Cite
|
Sign up to set email alerts
|

CCL2: a Chemokine Potentially Promoting Early Seeding of the Latent HIV Reservoir

Abstract: There are currently over 35 million people living with HIV worldwide, and we still have no vaccine or scalable cure. One of the difficulties with HIV is its ability to rapidly establish a viral reservoir in lymphoid tissues that allows it to elude antivirals and the immune system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…The deleterious effects of chronic upregulation of IL-32 and IL-32-mediated chemokine expression may also expand beyond atherosclerosis. For instance, CCL-2 was recently shown to mediate early seeding of the HIV reservoir by recruiting a unique subset of CCR2/5+ CD4+ T-cells which become infected and form a significant reservoir for latent infection [ 58 ]. Similar studies were also reported on CXCL-1 (an IL-32 induced chemokine) on the enhancement of HIV replication [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The deleterious effects of chronic upregulation of IL-32 and IL-32-mediated chemokine expression may also expand beyond atherosclerosis. For instance, CCL-2 was recently shown to mediate early seeding of the HIV reservoir by recruiting a unique subset of CCR2/5+ CD4+ T-cells which become infected and form a significant reservoir for latent infection [ 58 ]. Similar studies were also reported on CXCL-1 (an IL-32 induced chemokine) on the enhancement of HIV replication [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…One marker, CCL2, correlated to HIV infection and was elevated in HIV‐positive PwH. CCL2 is a prominent cytokine produced after HIV infection and also promotes the viral persistence 36 . And CCL2 plays also a dominant role in the development of osteoarthritis pain 37 .…”
Section: Discussionmentioning
confidence: 99%
“…CCL2 is a prominent cytokine produced after HIV infection and also promotes the viral persistence. 36 And CCL2 plays also a dominant role in the development of osteoarthritis pain. 37 As CCL2 was not elevated in HIV-negative PwH, CCL2 is obviously a more relevant marker for HIV infection than for (other) inflammation in PwH.…”
Section: Marker ß-Ngf Pwh ß-Ngf Conmentioning
confidence: 99%
“…1). CD4 + T cells from LT have been shown to rapidly produce CCL2 as an innate immune response during early stages of HIV infection, attracting infected CCR2/CCR5 + CD4 + central memory T cells (T CM ) towards the tissue, likely expanding the reservoir [11]. However, the impact of ART and acute infection resolution on long-term memory persistence in the body remains largely undefined.…”
Section: Tissue-reservoir Establishmentmentioning
confidence: 99%